How Might Climate Change Affect Economic Growth in Developing Countries? A Review of the Growth Literature with a Climate Lens - Lecocq, Franck (World Bank, Washington, DC, 2012)
This paper reviews the empirical and theoretical literature on economic growth to examine how the four components of the climate change bill, namely mitigation, proactive (ex ante) adaptation, reactive (ex post) adaptation, and ultimate damages of climate change affect growth, especially in developing countries. The authors consider successively the Cass-Koopmans growth model and three major strands of the subsequent literature on growth: with multiple sectors, with rigidities, and with increasing returns. The paper finds that although the growth literature rarely addresses climate change per se, some issues discussed in the growth literature are directly relevant for climate change analysis. Notably, destruction of production factors, or decrease in factor productivity may strongly affect long-run equilibrium growth even in one-sector neoclassical growth models; climatic shocks have had large impacts on growth in developing countries because of rigidities; and the introducing increasing returns has a major impact on growth dynamics, in particular through induced technical change, poverty traps, or lock-ins. Among the most important gaps identified in the literature are lack of understanding of the channels by which shocks affect economic growth, lack of understanding of lock-ins, heavy reliance of numerical models assessing climate policies on neoclassical-type growth frameworks, and frequent use of an inappropriate "without climate change" counterfactual.